Saxony's capital Dresden: On the way to become Eastern Germany's first Innovative Milieu? - Klaus-Heiner Röhl (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2000)
In this paper, the chances of Saxony's capital city Dresden to become Eastern Germany's first high-tech-region is discussed. A presentation of the theoretical background of innovative milieux is followed by an overview of the region's universities, R&D institutes and other facilities relevant for milieu formation. Afterwards, the establishment of high-tech enterprises in the Dresden area is analyzed. The paper concludes giving a view of the region's further development potential.
Keywords: 330; Hochtechnologiesektor; Innovation; Forschungskooperation; Region; Unternehmensnetzwerk; Technologiezentrum; Dresden